Sapphire-Based Dammann Gratings for UV Beam Splitting - Qian-Kun Li; Qi-Dai Chen; Li-Gang Niu; Yan-Hao Yu; Lei Wang; Yun-Lu Sun; Hong-Bo Sun (IEEE Photonics Journal)
We report sapphire-based Dammann gratings (DGs) for ultraviolet (UV) beam (266 nm) splitting, which is fabricated via femtosecond laser direct writing assisted with subsequent wet etching. By applying 400-nm-wavelength laser processing followed by wet etching, smooth surface morphology, together with well-tailored geometry, was obtained. These DGs generated 2 × 2, 3 × 3, 4 × 4, and 5 × 5 spot sources in the fan-out as designed and exhibited diffraction efficiency of 59.26%, 39.53%, 44.68%, and 55.37%, respectively, comparable with theoretical values. Such sapphire-based DGs show great potential in UV beam shaping, UV beam splitting, and laser parallel microprocessing.